2010
DOI: 10.1111/j.1365-2966.2010.16664.x
|View full text |Cite
|
Sign up to set email alerts
|

Small-spatial-scale variations of nebular properties and the abundance discrepancy in three Galactic H ii regions★

Abstract: We present the results of long‐slit spectroscopy in several slit positions that cover different morphological structures of the central parts of three bright Galactic H ii regions: M8, M17 and NGC 7635. We study the spatial distributions of a large number of nebular parameters, such as the extinction coefficient, line fluxes, physical conditions and ionic abundances at the maximum spatial resolution attainable with our instrumentation. Particularly, our goal is to study the behaviour of the abundance discrepan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 63 publications
3
14
0
Order By: Relevance
“…4. Mesa-Delgado & Esteban (2010) found C/H ratios between 8.6 to 9.0 dex in several zones of NGC 7635, indicating an abnormally high abundance of this element. However, the comparison of the C/H ratios included in Table 12 indicates that the values we determine from our new observations are consistent with those expected from the abundance gradient.…”
Section: Ngc 7635mentioning
confidence: 92%
See 1 more Smart Citation
“…4. Mesa-Delgado & Esteban (2010) found C/H ratios between 8.6 to 9.0 dex in several zones of NGC 7635, indicating an abnormally high abundance of this element. However, the comparison of the C/H ratios included in Table 12 indicates that the values we determine from our new observations are consistent with those expected from the abundance gradient.…”
Section: Ngc 7635mentioning
confidence: 92%
“…4 -show larger values of n e . Rodríguez (1999), Moore et al (2002b) and Mesa-Delgado & Esteban (2010) Table 3. continued Figure 4), so the determination is highly confident.…”
Section: Physical Conditionsmentioning
confidence: 99%
“…It is also evidenced by the presence of dense (≈ 10 3 − 10 4 cm −3 ; e.g. Mesa-Delgado & Esteban 2010;Moore et al 2002a;Esteban et al 2016) bright-rimmed structures around the Bubble Nebula (one of which is even penetrated into the bubble; e.g. Moore et al 2002a), whose "elephant trunk" morphology is typical of H ii regions expanding into dense molecular clouds (e.g.…”
Section: Bubble Nebula and Bd+60 • 2522mentioning
confidence: 99%
“…From intermediate and high resolution spectroscopy, several works have found that the ADF(O 2+ ) is always between 0.1 and 0.3 dex in Galactic and extragalactic H ii regions (see e.g. Esteban et al 2002;Tsamis et al 2003;Esteban et al 2004;López-Sánchez et al 2007;Mesa-Delgado et al 2008;Esteban et al 2009;Mesa-Delgado & Esteban 2010). García-Rojas & Esteban ( 2007) argued that the AD problem in H ii regions seems to be consistent with the predictions of the temperature fluctuation paradigm proposed by Peimbert (1967) and parametrized by the mean square of the spatial variations of temperature, the so-called t 2 parameter.…”
Section: Abundance Discrepancy Problemmentioning
confidence: 99%